Solving Systems of Linear Equations by the Sub. Method

Rebecca1

New member
Joined
Oct 2, 2005
Messages
1
Help! I need a explanation of the Subtitution Method in laymans terms.

Example of a problem: y=-x-1
4x-3y=24
Solution:

Step 1. Solve either of the equations for one variable in terms of the other. Apparently that one was done.

Step 2. Substitute the expression from step 1 into the other equation.
Subtitute the expression -x-1 for y in the other equation.

y=-x-1 4x-3y= 24 :?:

4x-3(-x-1) =24


I need some help with this laguage. Don't speak or understand algebra well. :? :(

Rebecca1
 

stapel

Super Moderator
Staff member
Joined
Feb 4, 2004
Messages
15,943
Solve the second equation, now in the form "4x - 3(-x - 1) = 24", for the value of x. Plug this value in for x in either of the original equations. Solve for y.

Eliz.
 
Top